DO UNDERGRADUATE PHYSICS STUDENTS STUDYING ABROAD NEED OPTIMISM? A CROSS-COUNTRY CASE STUDY - Putra, Rahman Pranovri; Ramadhanti, Auliya; Setiawati, Farida Agus; Azizah, Hanna Jessica Al; Puhka, Prakash (LPPM Universitas Jambi, 2024)
This pioneering study endeavors to paint a vivid portrait of optimism among physics undergraduate students pursuing studies abroad, illuminating the multifaceted dimensions of their academic and personal journey. Employing a qualitative case study approach, the research delves deep into the lived experiences of five purposively sampled participants, unraveling the intricate interplay between optimism, self-confidence, and social support networks. Through semi-structured interviews, the study unveils a compelling narrative of resilience and determination, as physics students abroad exhibit unwavering optimism in navigating the challenges inherent in their academic pursuits. Notably, participants demonstrate a profound sense of self-assurance, fostering a supportive environment characterized by mutual respect and camaraderie among peers. Moreover, the study sheds light on the pivotal role of external support systems, ranging from familial encouragement to mentorship from teachers, in bolstering students' resolve and fortitude. By focusing on physics undergraduate students hailing from Indonesia and studying across diverse international landscapes, this research offers a novel lens through which to understand the transformative power of optimism in transcending geographical and cultural boundaries. As such, the findings underscore the critical importance of fostering an optimistic mindset among students embarking on international academic endeavors, advocating for tailored support mechanisms that nurture self-efficacy, self-esteem, and social connectedness. Ultimately, this study serves as a clarion call for educational institutions and support service providers to prioritize holistic strategies aimed at cultivating and sustaining optimism among physics undergraduates pursuing studies abroad, thereby empowering them to thrive in the face of adversity and realize their full academic potential.